Examining Factors Affecting Gen Z’s Career Success in Surabaya - Haryanto, Ivy Jocelyn; Ongkowijoyo, Gracia (Jurnal Maksipreneur, 2025)
This research examines the factors that influence Generation Z’s career success in Surabaya. It focuses on the roles of networking and personal branding with social capital as a mediating variable. The Indonesian job market has shown increasing instability for young professionals in recent years, with Surabaya facing a higher-than-average youth unemployment rate. Gen Z, once seen as a demographic advantage for the country, is at a crucial juncture where it could become either a demographic asset or a burden. This study investigates how networking and personal branding affect career outcomes through social capital. Quantitative research was conducted through a survey of 108 Gen Z graduates in Surabaya, aged 24 to 28, all with at least three years of work experience, using purposive sampling. Data was collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that networking and personal branding significantly influence career success, while also enhancing social capital. Social capital has a positive influence on career success and significantly mediates the effects of personal branding and career success. These findings indicate that Gen Z should not only emphasize technical skills but also invest in building their networks and personal brands to enhance their career success. The research recommends creating university programs that focus on relationship-building skills, digital branding, and social capital development to improve the career growth of Gen Z in Indonesia.